Ultrafast multiphoton transient absorption of β-carotene - Buckup, Tiago; Weigel, Alexander; Hauer, Jürgen; Motzkus, Marcus (Chemical physics, 2010)
Multiphoton spectroscopy is able to directly excite electronic states, which are one-photon forbidden. Under single photon conditions, such one-photon forbidden states are exclusively populated via internal relaxation. Hence, transient absorption with two-photon excitation has the potential of clarifying complex relaxation networks by using aimed excitation. In this work we exploited ultrafast two-photon spectroscopy to investigate the excitation of dark states of β-carotene in solution. After direct excitation of the vibronic manifold of S12Ag- from S0 via two-photon transition, the characteristic internal conversion via hot-S1→S1→S0 was observed in the respective spectral region. Additional slow dynamics in the blue-wing of excited-state absorption (ESA) and in the NIR were detected, which is not directly observable with one-photon excitation transient absorption. These features are associated here to resonant multiphoton processes, which lead simultaneously to ultrafast intersystem crossing between singlet and triplet systems as well as to excitation of doublet states. Furthermore, we identify a 340-400fs relaxation component in the near-infrared region after two-photon resonant excitation and discuss the role of additional dark states (3Ag- and 1Bu-) in this process.